PESANTREN AND CHALLENGES OF MODERNITY A Critical View Of Pesantren – Based School Model for Education in Modernity - Yusuf, Ahmad (Pascasarjana IAIN Kudus, 2019)
This research aims to create critical thinking about innovation in the pesantren system. This research is a descriptive study using a qualitative approach to investigate social change, Pesantren's perception of modernity by finding information from documents or research findings related to Pesantren and its challenges in modernity. Of course the number of pesantren integrated with public schools or vice versa continues to increase. Pesantren-based Schools nationally began to be declared in 2008 with 25 members and at the end of 2015 recorded an increase to 302. This proves that critical thoughts, attitudes that are innovative, adaptive, and accommodate the development of pesantren must continue to be developed so that pesantren develop. always relevant and able to respond to social changes that are so fast and unexpected. The results of this study indicate that pesantren have the ability to adapt to the development of more times and occur so quickly. The pesantren has demonstrated its ability in the era of modernity and difficulties, so that it does not only use religious and religious sources of knowledge in Islam but also